The impact of managerial ability on crisis-period corporate investment - Andreou, Panayiotis; Karasamani, Isabella; Louca, Christodoulos; Ehrlich, Daphna (My University, 2017)
In this study, we document a strong positive relation between pre-crisis managerial ability and corporate investment during the crisis period, which remains robust in the presence of a large array of control variables capturing corporate governance attributes, executive compensation incentives and CEO characteristics. This relationship was prevalent only among firms with CEOs that had general managerial skills, rather than firm specific skills. Our results also show that the positive relationship between managerial ability and corporate investment was supported by the capacity of such firms to secure greater financing and be less vulnerable to financial constraints during the crisis. Finally, we find that, on average, the stock market evaluates crisis-period investments positively, yet this effect is evident solely among firms characterized by high pre-crisis managerial ability. Overall, the results are consistent with the view that high managerial ability helps to mitigate under investment problems during a crisis which in turn increases firm value.
Keywords: Firm value; Underinvestment problems; Financing; Corporate investment; Generalist CEOs; Managerial ability